Tourism service quality and tourism product availability on the loyalty of international tourists - Rahmiati, Filda; Othman, Norfaridatul Akmaliah; Bakri, Mohammed Hariri; Ismail, Yunita; Amin, Grace (Korea Distribution Science Association (KODISA), 2020)
Tourist loyalty is created through good tourism service quality and the availability of tourism products. This study discussed the various attributes of tourism service quality, namely, tour agents, efficient personnel, accessible transportation, and information service quality. Whereas for tourism product availability attributes were varieties of product availability, wide selection of tour agents and tourist products, and wide variety of amenity services. As a general rule, the minimum is to have at least five times as many observations as the number of variables to be analyzed, and the more acceptable sample size would have a 10:1 ratio. A total of 424 questionnaires were returned, with 35 removed due to errors. Finally, 389 questionnaires respondents were used via accidental sampling method through the distribution of questionnaires to foreign tourists at Soekarno Hatta International Airport. In addition, AMOS 7.0 software is used to test models in confirmatory factor analysis (CFA) as well as hypothetical testing using structural equation modeling (SEM). The results showed that all hypotheses were accepted, except for the effect of tourism service quality on tourist loyalty in Indonesia. This research aims to contribute significantly to the existing knowledge of tourism, specifically from a foreign tourist perspective in Indonesia.